2023
DOI: 10.1111/1467-8500.12581
|View full text |Cite
|
Sign up to set email alerts
|

Backloading to extinction: Coping with values conflict in the administration of Australia's federal biodiversity offset policy

Abstract: Policy-makers are frequently required to consider and manage conflicting public values. An example of this in the environmental domain is biodiversity offset policy, which governments worldwide have adopted as a mechanism to balance environmental protection with socio-economic development. However, little work has examined administrative practices underpinning biodiversity offset policy implementation, and how the adoption of coping strategies to manage value conflicts may influence resulting policy outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…The quote above suggests an apparent disavowal of biodiversity offsets (Evans, 2023;Lapeyre, et al, 2015), but the careful use of language is also illustrative of recent discussion around so-called voluntary biodiversity credits (NatureFinance and Pollination, 2023;WEF, 2022). The term "biodiversity credit" has often been used to refer to the units of biodiversity gains that are traded to offset biodiversity losses within regulated regimes (Carroll, et al, 2008), but has been more recently (re)defined by industry proponents as tradeable biodiversity units that aim to "… achieve a net positive outcome without directly offsetting negative impacts elsewhere" (NatureFinance and Pollination, 2023, p. 16) and differ from offsets via "…the intention of the purchase and the claims that are made around that purchase" (WEF 2022, p. 4, emphasis in original).…”
Section: The Discursive Object Of Innovation: the Tradable Biodiversi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The quote above suggests an apparent disavowal of biodiversity offsets (Evans, 2023;Lapeyre, et al, 2015), but the careful use of language is also illustrative of recent discussion around so-called voluntary biodiversity credits (NatureFinance and Pollination, 2023;WEF, 2022). The term "biodiversity credit" has often been used to refer to the units of biodiversity gains that are traded to offset biodiversity losses within regulated regimes (Carroll, et al, 2008), but has been more recently (re)defined by industry proponents as tradeable biodiversity units that aim to "… achieve a net positive outcome without directly offsetting negative impacts elsewhere" (NatureFinance and Pollination, 2023, p. 16) and differ from offsets via "…the intention of the purchase and the claims that are made around that purchase" (WEF 2022, p. 4, emphasis in original).…”
Section: The Discursive Object Of Innovation: the Tradable Biodiversi...mentioning
confidence: 99%
“…This in-depth single case study generates "local knowledge from which can be derived unique understanding" of the financialisation inherent in biodiversity finance that respects its situated complexity (Bazeley, 2013, p. 410). Key examples of Australia's long history with environmental markets include the world's first mandatory national carbon trading scheme (IPART, 2013), the first national scheme that enabled carbon credits to be generated from agricultural, forestry and other forms of land management (Evans, 2018;van Oosterzee et al, 2014), and the use of biodiversity offsetting since at least the early 2000's (Evans, 2023;Maron et al, 2015). The Australian federal government is actively encouraging for-profit conservation, including through what has been called the world's first legislated national voluntary biodiversity market (NatureFinance and Pollination, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For example, streamlining planning often leads to measuring biodiversity using simplified assessment tools which are easily applied by consultants, leading to these systems delivering nature improvements designed to optimise the delivery of the specific biodiversity features chosen in policy, potentially driving homogenisation of habitats (Lave et al, 2010; Rampling et al, 2023; Tillman & Matthews, 2023). These and other governance challenges such as capacity shortages in regulators have led to systemic implementation failures (Bezombes et al, 2019; Evans, 2017, 2023; Samuel, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Examples from around the world include regulators being unable to send staff to assess offset sites or conduct basic compliance checks (Carver & Sullivan 2017;Samuel 2021). Evans (2023) demonstrated that overstretched regulators in the Australian statutory offsetting system have developed behaviours for deferring the most complex aspects of decisions around offsets until after developments are approved, when opportunities for public accountability and engagement become severely restricted. This is in part because of a lack of capacity to deal with reconciling different values expressed by stakeholders at the public consultation stage.…”
Section: Introductionmentioning
confidence: 99%